2019
DOI: 10.1159/000499052
|View full text |Cite
|
Sign up to set email alerts
|

Delays in the Diagnosis and Treatment of Tuberculous Lymphadenitis in Low-Incidence Countries: A Systematic Review

Abstract: Early detection and treatment of tuberculosis (TB) is essential to achieve the goals appointed in the WHO End TB Strategy. Tuberculous lymphadenitis (TBLA) is the most common manifestation of extrapulmonary TB, but the diagnosis can be challenging in low-incidence countries due to sparse and inconsistent clinical features, resulting in delay. We aimed to summarize and discuss the current literature on patient delay, health care delay, and total delay (i.e., time to first health care contact, diagnosis, and tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
(72 reference statements)
0
13
0
Order By: Relevance
“…As mentioned, it is assumed that the diagnosis of TBLA in Denmark is often delayed and not considered before late into the course of disease. The disease is rare, and a high index of suspicion is required (Mathiasen et al, 2019a;Mathiasen et al, 2019b). This is also supported by the substantial health care delay of a median of 42 days (IQR 16-82), which is comparable to a recent systematic review (Mathiasen et al, 2019b).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…As mentioned, it is assumed that the diagnosis of TBLA in Denmark is often delayed and not considered before late into the course of disease. The disease is rare, and a high index of suspicion is required (Mathiasen et al, 2019a;Mathiasen et al, 2019b). This is also supported by the substantial health care delay of a median of 42 days (IQR 16-82), which is comparable to a recent systematic review (Mathiasen et al, 2019b).…”
Section: Discussionmentioning
confidence: 82%
“…The disease is rare, and a high index of suspicion is required (Mathiasen et al, 2019a;Mathiasen et al, 2019b). This is also supported by the substantial health care delay of a median of 42 days (IQR 16-82), which is comparable to a recent systematic review (Mathiasen et al, 2019b). It is important that all patients with TBLA are screened for pulmonary symptoms and examined with chest radiographs to preclude contagious TB.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In most low-incidence countries, TBLA is rare and the clinician not used to diagnose this disease manifestation. Our recent review suggests that TBLA patients experience delays in both presentation, diagnosis and treatment [5]. The diagnosis may be complicated due to difficulties in obtaining good samples for microbiological examination [36], e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, this may result in delays in diagnosis which potentially increases the morbidity and mortality for the affected patients and constitutes sources of Mycobacterium tuberculosis (Mtb) transmission in undiagnosed patients with concurrent pulmonary infection [5,6]. In a recent systematic review, we demonstrated that TBLA patients have a mean health care delay of up to as many as 94 days in low-incidence, high-income countries [5]. Furthermore, EPTB has been associated with an increased long-term mortality [7,8].…”
Section: Introductionmentioning
confidence: 99%